Mesenchymal stromal cells induce inhibitory effects on hepatocellular carcinoma through various signaling pathways - Ai, Jafar; Ketabchi, Neda; Verdi, Javad; Gheibi, Nematollah; Khadem Haghighian, Hossein; Kavianpour, Maria (Cancer cell international, 2019)
Hepatocellular carcinoma (HCC) is the most prevalent type of malignant liver disease worldwide. Molecular changes in HCC collectively contribute to Wnt/β-catenin, as a tumor proliferative signaling pathway, toll-like receptors (TLRs), nuclear factor-kappa B (NF-κB), as well as the c-Jun NH2-terminal kinase (JNK), predominant signaling pathways linked to the release of tumor-promoting cytokines. It should also be noted that the Hippo signaling pathway plays an important role in organ size control, particularly in promoting tumorigenesis and HCC development. Nowadays, mesenchymal stromal cells (MSCs)-based therapies have been the subject of in vitro, in vivo, and clinical studies for liver such as cirrhosis, liver failure, and HCC. At present, despite the importance of basic molecular pathways of malignancies, limited information has been obtained on this background. Therefore, it can be difficult to determine the true concept of interactions between MSCs and tumor cells. What is known, these cells could migrate toward tumor sites so apply effects via paracrine interaction on HCC cells. For example, one of the inhibitory effects of MSCs is the overexpression of dickkopf-related protein 1 (DKK-1) as an important antagonist of the Wnt signaling pathway. A growing body of research challenging the therapeutic roles of MSCs through the secretion of various trophic factors in HCC. This review illustrates the complex behavior of MSCs and precisely how their inhibitory signals interface with HCC tumor cells.